The Effect of Variety and Gibberellic acid and Brassinolide and their Interaction on Some of The Chemical Characteristics and Total chlorophyll of the plant Dill Anethum graveolens L. (Baghdad Science Journal, 2025)
The experiment was carried out to study the effect of variety and gibberellic acid in concentration (0 and 50)mg.lat-1 and BL in five concentration (0, 0.50 ,1 ,2 and 3)mg.ltr-1 and their interaction in some chemical Characteristics and total chlorophyll for Dill plant . the experiment designed according Randomized Complete Block Design (RCBD) and three replicates per treatment, compared to the average using less significant difference at the level of probability (0.05) , the results showed the following:-The effect of brassinolide with it,s concentrations led to obtain a significant increase in all the studied characteristics, so the superiority of the concentration of 2 mg.L-1 of brassinolide in each of Ca, Mg,Fe, and total chlorophyllThe effect of gibberellic acid with it,s two concentrations led to obtain a significant increase in all the studied characteristics and the highest in of the concentrate at 50 mg.L-1in two local and hol and varieties.The all bilateral interactions had a significant effect on all the studies characteristics with superiority of the treatment (2 from brassinolide, 50 from gibberellic acid) mg. L-1 in the ratio of Ca, Mg,Fe and total chlorophyll.The tripleinter actions led not to obtain a significant increase in all of the study of significant factors